Anti-Synthetase Syndrome-Related Interstitial Lung Disease With Anti-PL-12 Antibodies - Elferjani, Belqis (Cureus, 2021)
Anti-synthetase syndrome usually comprises interstitial lung disease, myositis, arthralgias, and Raynaud phenomenon. The anti-PL-12 antibody is directed against the enzyme alanyl-tRNA synthetase and has been associated with interstitial lung disease in the absence of inflammatory myositis. We report the case of a 33-year-old woman with complaints of progressive dyspnea, a persistent dry cough, along with intermittent low-grade fever for a few months. A computed tomography (CT) scan of the chest showed the presence of patchy bilateral airspace opacities and infiltrates. It also showed significant mediastinal and hilar lymphadenopathy. Bronchoscopy with transbronchial biopsy was performed, and histopathology changes were consistent with connective tissue disease related to interstitial lung disease. Further workup revealed the presence of anti-PL-12 antibodies. This case illustrates a rare association of interstitial lung disease with the anti-PL-12 antibody.